End-to-end deterministic networking architecture and key technologies - Peng LIU; Zongpeng DU; Yongjing LI; Lu LU; Xiaodong DUAN (Dianxin kexue)
New services such as remote control and cloud AR/VR, have put forward higher bandwidth and latency requirements than traditional network.6G-oriented network evolution needs end-to-end deterministic networking technology support.In view of the lack of global consideration of end-to-end latency guarantee in current technical standard research, it was pointed out that deterministic networking needs to solve the problem of single hop and global latency at the same time.An end-to-end deterministic networking architecture was built, as well as deterministic networking technical schemes across networking domain and protocol layer was proposed.Finally, according to the current difficulties of deterministic networking development, the corresponding promotion suggestions were put forward.